Endobronchial ultrasound-guided versus conventional transbronchial needle aspiration: time to re-evaluate the relationship? - Medford, Andrew RL (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
Conventional transbronchial needle aspiration (cTBNA) has a long history over three decades of utility for mediastinal sampling in lung cancer (1) especially in more bulky disease and can achieve high yields (nearly 80% or above) even in relatively new services (2). It has also been utilised in the diagnosis of benign mediastinal disease (3). The attractiveness of cTBNA is that it can be performed at the same sitting as conventional bronchoscopy by a respiratory physician/interventional pulmonologist under conscious sedation in an endoscopy suite without needing a thoracic surgeon, operating theatre, theatre team and associated expenses (4). A common application of cTBNA is to select out those patients with multi-station or bulky N2 disease who are not suitable for radical therapy but would be suitable for oncological therapies and thereby avoiding the invasiveness and cost of mediastinoscopy for diagnosis alone. More recently, in the last decade or so (5,6), endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has come to the fore which has prompted a re-evaluation of all mediastinal sampling and staging techniques (4,7). There has also been further interest in the utility of both cTBNA and EBUSTBNA beyond lung cancer in diagnosis of treatable benign mediastinal disease such as tuberculosis (3,6).